The Green Revolution reconsidered: the impact of high-yielding rice varieties in South India - Hazell, Peter B. R.; Ramasamy, C.; Aiyasamy, P. K. (International Food Policy Research Institute, 1991)
Agricultural growth is essential for fostering economic development and feeding growing populations in most developing countries. As land and water become increasingly scarce, this growth will depend more and more on yield-increasing technological changes of the green revolution" type. A major concern is how these technologies will affect the poor. If the poor are left behind and rural inequalities worsen, agricultural growth may fail to achieve its intended objectives... Peter Hazell and C. Ramasamy, along with several associates , find that landless laborers and small-scale farmers gained proportionally as much as large-scale farmers. Despite initial lags in adoption of these varieties by small-scale farmers, virtually all farmers eventually adopted them and significantly increased their productivity." (Excerpts from text)"